Cash flow analysis: Red flag indicators of financial distress in Malaysian companies - Binti Mohd Ali, Norfisah; Mat Rahim, Nurhazrina (Edelweiss Applied Science and Technology, 2024)
The unprecedented coronavirus disease (COVID-19) pandemic devastated the world from early 2020 caused an economic decline impacting numerous companies worldwide, including Malaysia. Thus, companies should foresee financial distress to better prepare and establish mitigating measures for future challenges. One method to examine the financial situation of a company is by investigating the cash flow information. The study aims to investigate the relationship between cash flow patterns and financial distress. Data were gathered from 24 public listed companies in Bursa Malaysia from 2009 to 2019 and the study applied the binary logistic regression and chi-square analysis test for independence. The results indicated that companies with a negative cash flow from operating activities would more likely experience financial distress due to the inability to generate sufficient cash to cover operations, future investment, and long-term debt. Additionally, distressed companies tend to discard fixed assets/investments, or drawdown borrowings to relieve the cash deficit.